Regionalismus und historische Identität –: Transnationale Dialoge zur Geschichte Nord-/ Ost-/ Asiens seit den 1990er Jahren - Spakowski, Nicola (Comparativ, 2008)
Since the Asian financial crisis of 1997 initiatives of regional cooperation and integration have proliferated in Asia. However, these initiatives are usually based on government agreements and business networks only. They are rarely substantiated by what scholars of regionalism call a “cognitive” or “imagined” region. This article explores contemporary transnational dialogues of (mainly Northeast) Asian intellectuals on the history of Asia as an important dimension of a “cognitive” region. Three forms of dialogue are discussed and compared: textbook dialogue, academic dialogue and the dialogue of critical intellectuals on the nature of Asian modernity. The analysis shows that the persistence of nationalist perspectives is a major obstacle to constructing a shared view of Asian history. The transcendence of nationalist points of view, on the other hand, requires a level of reflexivity and epistemological awareness that also reveals the constructed nature of any definition of “Asia”. Asia as a category remains contested and unstable.